PENGGUNAAN ALGORITMA PETURB AND OBSERVE (PNO) DALAM STUDI PENGGUNAAN SEPIC DAN ZETA KONVERTER UNTUK MAXIMUM POWER POINT TRACKER (MPPT) PADA PHOTOVOLTAIC STATIS - Arfah, Efrita; Priananda, Ciptian Weried; Haryudo, Subuh Isnur (Universitas Negeri Surabaya, 2017)
Photovoltaic (PV) is one of the equipments used to convert solar energy that can be used as an alternative source of renewable energy. The effectiveness of PV can be improved by operating the the PV panel at optimum point by using the MPPT algorithm. This study will present a comparative study of the use of the SEPIC converter and Zeta converters for applications using MPPT algorithm Peturb and Observe (PNO). The results of the characteristics of the two converters will be compared, while the parameters are compared include input-output voltage, voltage ripple and input-output power.